Behaviour of reinforced concrete frame at ultimate limit state - Abu Bakar, Mohd. Azmir (2005)
The objective of this study is to understand reinforced concrete beam-column connection behaviour toward ultimate limit state using ATENA 2D, a non linear finite element analysis. Based on previous studies, the behaviour of beam-column with semi rigid connection in steel structure has shown a very different behaviour during elastic range and beyond yield point, because of phenomenon called moment shedding. Using the same approach, analytical studies on the response of concrete framed structures at ultimate limit have been conducted. This study shows that when the reinforced concrete structures reach the ultimate limits state, the column will behave similar to an axial loaded column. This outcome is a result of redistribution of end moment near collapse condition, where moment has been transfered to nearby structure component, in this study to a beam component. With the phenomenon occurs near ultimate limit state, a simplified design approach can be formed for reinforced concrete designed.